Epitomize Your Photos. (6th February 2012) - Vajda, Peter; Ivanov, Ivan; Lee, Jong-Seok; Ebrahimi, Touradj
Abstract : With the rapid growth of digital photography, sharing of photos with friends and family has become very popular. When people share their photos, they usually organize them into albums according to events or places. To tell the story of some important events in one's life, it is desirable to have an efficient summarization tool which can help people to receive a quick overview of an album containing large number of photos. In this paper, we present and analyze an approach for photo album summarization through a novel social game "Epitome" as a Facebook application. This social game can collect research data, and, at the same time, it provides a collage or a cover photo of the user's photo album, while the user enjoys playing the game. The proof of concept of the proposed method is demonstrated through a set of experiments on several photo albums. As a benchmark comparison to this game, we perform automatic visual analysis considering several state-of-the-art features. We also evaluate the usability of the game by making use of a questionnaire on several subjects who played the "Epitome" game. Furthermore, we address privacy issues concerning shared photos in Facebook applications.